Brief Theoretical Overview of Bi-Fe-O Based Thin Films - Misiurev, Denis; Holcman, Vladimír; Kaspar, Pavel (MDPI, 2022)
This paper will provide a brief overview of the unique multiferroic material Bismuth ferrite (BFO). Considering that Bismuth ferrite is a unique material which possesses both ferroelectric and magnetic properties at room temperature, the uniqueness of Bismuth ferrite material will be discussed. Fundamental properties of the material including electrical and ferromagnetic properties also will be mentioned in this paper. Electrical properties include characterization of basic parameters considering the electrical resistivity and leakage current. Ferromagnetic properties involve the description of magnetic hysteresis characterization. Bismuth ferrite can be fabricated in a different form. The common forms will be mentioned and include powder, thin films and nanostructures. The most popular method of producing thin films based on BFO materials will be described and compared. Finally, the perspectives and potential applications of the material will be highlighted.

This paper will provide a brief overview of the unique multiferroic material Bismuth ferrite (BFO). Considering that Bismuth ferrite is a unique material which possesses both ferroelectric and magnetic properties at room temperature, the uniqueness of Bismuth ferrite material will be discussed. Fundamental properties of the material including electrical and ferromagnetic properties also will be mentioned in this paper. Electrical properties include characterization of basic parameters considering the electrical resistivity and leakage current. Ferromagnetic properties involve the description of magnetic hysteresis characterization. Bismuth ferrite can be fabricated in a different form. The common forms will be mentioned and include powder, thin films and nanostructures. The most popular method of producing thin films based on BFO materials will be described and compared. Finally, the perspectives and potential applications of the material will be highlighted.
Brief Theoretical Overview of Bi-Fe-O Based Thin Films
Keywords: Bismuth ferrite; multiferroic; thin film; ferroelectric; magnetic; PDL; ALD; leakage current; hysteresis; Bismuth ferrite; multiferroic; thin film; ferroelectric; magnetic; PDL; ALD; leakage current; hysteresis